2009
DOI: 10.1139/x09-128
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of leaf energy and resource investment of invasive Berberis thunbergii and co-occurring native shrubs

Abstract: Photosynthetic energy gain and biomass energy and resource investment represent trade-offs between potential enhancements and limitations to plant productivity, respectively. We compared these characteristics in the exotic invasive Berberis thunbergii DC. with that of co-occurring natives Kalmia latifolia L. and Vaccinium corymbosum L. in a northeastern United States forest. We hypothesized that invasion by B. thunbergii could be facilitated by a lower leaf construction cost (CC) and reduced leaf nitrogen cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Leaf construction cost (CC) quantifies the amount of glucose equivalents required to construct a leaf in terms of carbon skeletons, reductant, and ATP, excluding additional costs for maintenance and substrate transport (Williams, Field & Mooney ). Leaf CC mass (g glucose g −1 leaf mass) was determined using a biochemical approximation (Vertregt & Penning de Vries ; Poorter ; Boyd, Xu & Griffin ):CCnormalmass=false(1.041+5.077Cmassfalse)false(10.67Ashfalse)+5.325Nnormalmass…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf construction cost (CC) quantifies the amount of glucose equivalents required to construct a leaf in terms of carbon skeletons, reductant, and ATP, excluding additional costs for maintenance and substrate transport (Williams, Field & Mooney ). Leaf CC mass (g glucose g −1 leaf mass) was determined using a biochemical approximation (Vertregt & Penning de Vries ; Poorter ; Boyd, Xu & Griffin ):CCnormalmass=false(1.041+5.077Cmassfalse)false(10.67Ashfalse)+5.325Nnormalmass…”
Section: Methodsmentioning
confidence: 99%
“…Leaf construction cost (CC) quantifies the amount of glucose equivalents required to construct a leaf in terms of carbon skeletons, reductant, and ATP, excluding additional costs for maintenance and substrate transport (Williams, Field & Mooney 1989). Leaf CC mass (g glucose g À1 leaf mass) was determined using a biochemical approximation (Vertregt & Penning de Vries 1987;Poorter 1994;Boyd, Xu & Griffin 2009): CC mass ¼ ðÀ1:041 þ 5:077C mass Þð1 À 0:67AshÞ þ 5:325N mass where C mass is leaf carbon concentration, Ash is leaf ash concentration (proxy for mineral concentration; Vertregt & Penning de Vries 1987), and N mass is leaf nitrogen concentration (all in g g À1 ).…”
Section: E a F S T R U C T U R A L A N D B I O C H E M I C A L C H mentioning
confidence: 99%
“…Demographic studies of temperate forest tree invasions suggest that invaders do not necessarily follow demographic or life history tradeoffs evident in the native flora, such as that between low-light survivorship and high-light growth (Martin et al, 2010) and between classic r/K strategies of fast growth and reproduction versus persistence (Closset-Kopp et al, 2007). Select comparative studies, often in habitats of limited light or nutrients, report invasive plants with seemingly superior performance compared with natives at a given metabolic or resource cost, including increased growth rates (Osunkoya et al, 2010), greater mean performance or trait plasticity (Funk, 2008;Godoy et al, 2012;Paquette et al, 2012), greater photosynthetic rates at lower respiratory costs (Pattison et al, 1998;McDowell, 2002) and greater resource-or energy-use efficiencies (Baruch & Goldstein, 1999;Nagel & Griffin, 2004;Funk & Vitousek, 2007;Boyd et al, 2009). All else being equal, these findings imply that invasive species are not constrained by the same tradeoffs as natives, leading to greater production given similar resource investments.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive plants have often higher PNUE [4,9,30], higher PEUE [8] or both higher PEUE and PNUE [6,10,12] than natives species. Also in their work comparing energy use strategy of an invasive species from populations of its native ranges and introduced ranges, Ref.…”
Section: Resource Utilization Efficiencymentioning
confidence: 99%
“…Studies comparing leaf traits of invasive plants and native plants have shown that invasive species have higher specific leaf area (SLA) [4,5], lower mass-based leaf construction cost (CC mass ) [4,[6][7][8], higher photosynthetic nitrogen use efficiency (PNUE) [3,4,9], higher photosynthetic energy use efficiency (PEUE) [8,10] and higher water use efficiency (WUE) [9,11] than native species. However, some studies have detected that there are no significant differences in CC mass [12], PNUE [8] and WUE [6,8] between invaders and natives. A recent study also suggests that the populations in the introduced range of an invasive species have evolved a higher PEUE and a shorter payback time but not lower CC mass than those in the native range [13].…”
Section: Introductionmentioning
confidence: 99%